Membrane potential, serum calcium and serum selenium decrease in preeclampsia subjects in Owerri - Nnodim, Johnkennedy; Emmanuel, Nwodo; Hope, Okorie; Nwadike, Constance; Ukamaka, Edward; Christian, Onah (Universa Medicina, 2017)
Background Pre-eclampsia is a serious hypertensive condition of pregnancy associated with high maternal and fetal morbidity and mortality. Women who have had pre-eclampsia have a greater risk of developing hypertension, stroke and ischemic heart disease in later life. The etiology of pre-eclampsia remains unclear. Placental insufficiency plays a key role in the progression of this disease. The aim of this study was to determine membrane potential, serum calcium and serum selenium levels in preeclampsia subjects in Owerri. MethodsA case control study involving 200 primigravida (100 preeclamptic and 100 apparently healthy) between the ages of 20 and 32 years attending General Hospital Owerri. Fasting venous blood was collected for the determination of serum selenium and serum calcium while membrane potential was calculated using the Nernst equation. The serum calcium was estimated using Randox Kit and serum selenium by atomic absorption spectrophotometry. The Independent Student t test was used for statistical analysis. ResultsThe results revealed that membrane potential and serum selenium as well as serum calcium were significantly decreased in preeclampsia when compared with the controls, at p<0.05. ConclusionOur study demonstrated that the decrease in membrane potential, serum calcium and serum selenium levels may play a critical role in the pathogenesis of pre-eclampsia. There may be a need for increasing the dietary intake of these essential trace metals during pregnancy to prevent pre-eclampsia in Owerri.